-4x-2x+11=6x-13

Simple and best practice solution for -4x-2x+11=6x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x-2x+11=6x-13 equation:


Simplifying
-4x + -2x + 11 = 6x + -13

Reorder the terms:
11 + -4x + -2x = 6x + -13

Combine like terms: -4x + -2x = -6x
11 + -6x = 6x + -13

Reorder the terms:
11 + -6x = -13 + 6x

Solving
11 + -6x = -13 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
11 + -6x + -6x = -13 + 6x + -6x

Combine like terms: -6x + -6x = -12x
11 + -12x = -13 + 6x + -6x

Combine like terms: 6x + -6x = 0
11 + -12x = -13 + 0
11 + -12x = -13

Add '-11' to each side of the equation.
11 + -11 + -12x = -13 + -11

Combine like terms: 11 + -11 = 0
0 + -12x = -13 + -11
-12x = -13 + -11

Combine like terms: -13 + -11 = -24
-12x = -24

Divide each side by '-12'.
x = 2

Simplifying
x = 2

See similar equations:

| -r^2=49-14r | | 1/2(x+3)=5 | | t=2h-2g | | 780=4t^2+7t+600 | | 63=x-.23x | | -4(3u-8)+2u=2(u+8) | | 49*2=3a-1a | | (9-d)*11=55 | | 4(3b-5)+2=-114 | | 5t=14 | | x^2=64forx | | 1/2(108+f)=73 | | 6m-27+18m=-10m+29 | | (49/100)-x^2=0 | | 8x+1=162 | | 6k^2+5k-4=0 | | (49/100)-x=0 | | 0=-lnx | | (4y+5)(y+3)=-4(4y+5) | | y=-1+(1-lnx) | | 15x-9=40x+1 | | 24x^2+2x=35 | | 5/6x+18+1/6x=6-3(x-4) | | (6+w)(3w-5)=0 | | 5x+1=7x-(3) | | y=18/-6 | | 175000.00+550x=35000.00+1680.00x | | 2x+18=116 | | y=1/2x+9 | | -7d+3=-3d+11 | | x-5/100x+2/3*5/100x=59 | | 0.5(6p-8)=17 |

Equations solver categories